PENGARUH TRANSPARANSI, KOMPETENSI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PEMERINTAH DESA DALAM PENGELOLAAN ALOKASI DANA DESA (Studi Empiris Pada Seluruh Desa Di Kecamatan Salo Kabupaten Kampar) - Muhammad Rosyidi; Nur Azlina; Adhitya Agri Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research was to identify and analyze about : 1) the effect Effect of transparancy on village government accountability in management of village fund. 2) Effect of competence on village government accountability in management of village fund. 3) Influence of internal control system on village government accountability in management of village fund. This study was conducted in all villages in Salo Sub-district, Kampar District, which amounted to 6 villages. Data used in this research is primary data with questionnaire as instrument. The method used in sample selection is purposive sampling. The number of samples in this study was 123 respondents. Hypothesis test used in this research is statistical t test. Data analyze technique used in this research is multiple linear analyze using Statistical product and service solution (SPSS) version 20.0. The results show that transparency, competence and internal control system have a positive effect on village government accountability in managing the village funds.Keywords : transparancy, competence, influence of internal control system, accountability